ChemInform Abstract: Syntheses, Characterization and Evaluation of Novel 2, 6‐Diarylpiperidin‐4‐ones as Potential Analgesic‐Antipyretic Agents. Issue 51 (23rd December 2014) - Tripathi, Purnima; Tripathi, Avinash C.; Chawla, Viney; Saraf, Shailendra K.
Abstract A series of N‐chloroacetyl‐3‐methyl‐2, 6‐diarylpiperidin‐4‐ones (III) and N‐(4‐methylpiperazino)acetyl‐3‐methyl‐2, 6‐diarylpiperidin‐4‐ones (V) are prepared and tested on their analgesic as well as antipyretic activities.